Leader mental model and organizational digital maturity: The dual intermediary effect of technology empowerment and organizational culture - Pan, Shoupei; Huang, Minghao (Edelweiss Applied Science and Technology, 2025)
This study examines the relationship between leadership mental models (LMMs) and organizational digital maturity, investigating the dual mediating effects of technical empowerment and organizational culture. Design/Methodology/Approach: A quantitative survey of 360 enterprises across various industries was conducted. Data were analyzed using structural equation modeling and bootstrap analysis to test direct and indirect effects, with additional multi-group analysis examining differences across organizational characteristics. Results indicate that LMMs significantly affect organizational digital maturity both directly (β = 0.384, p < 0.001) and indirectly through technical empowerment (β = 0.213, p < 0.01) and organizational culture (β = 0.175, p < 0.01). Organizational size moderates these effects, with stronger relationships observed in larger organizations. Multi-group analysis reveals significant variance across sectors, particularly in technology-intensive industries. The study confirms the importance of leadership cognitive frameworks in digital transformation processes, with technical capabilities and organizational culture serving as crucial mediating mechanisms. Practical Implications: Organizations pursuing digital transformation should develop appropriate leadership mental models while simultaneously fostering technical empowerment and a supportive organizational culture. Strategies should be tailored to organizational size and industry context to maximize digital maturity outcomes.